2008
DOI: 10.1002/jso.21042
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the optimal duration of chemotherapy in patients with colorectal liver metastases

Abstract: In responders to preoperative therapy, surgical resection should be considered after 2-4 months, when most patients have achieved maximal response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…According to a recent report, chemotherapeutic effect disappears after 4 months or more 21, supporting the present results. The tumor shrinkage rate also showed first-line chemotherapy to be the most effective and to be un-expectable though second to third line objectively.…”
Section: Discussionsupporting
confidence: 93%
“…According to a recent report, chemotherapeutic effect disappears after 4 months or more 21, supporting the present results. The tumor shrinkage rate also showed first-line chemotherapy to be the most effective and to be un-expectable though second to third line objectively.…”
Section: Discussionsupporting
confidence: 93%
“…In our case liver fibrosis with splenomegaly developed after 12 cycles of FOLFOX regimen. In the case of preoperative chemotherapy, the optimal duration is about 4 month at most to maximize therapeutic benefit, while avoiding hepatotoxicity (13). …”
Section: Discussionmentioning
confidence: 99%
“…Probably the optimum duration of preoperative chemotherapy, to maximise therapeutic benefi t while avoiding hepatotoxicity, is likely to be 4 months. White and colleagues [51] reported that patients experienced tumour reduction after 2-4 months of chemotherapy and little reduction thereafter, indicating that chemotherapy continued beyond 4 months has little therapeutic effect.…”
Section: How Can We Prevent Liver Injury?mentioning
confidence: 97%